2021
DOI: 10.3389/fonc.2021.709210
|View full text |Cite|
|
Sign up to set email alerts
|

Single-Cell Transcriptomics Reveals the Complexity of the Tumor Microenvironment of Treatment-Naive Osteosarcoma

Abstract: Osteosarcoma (OS), which occurs most commonly in adolescents, is associated with a high degree of malignancy and poor prognosis. In order to develop an accurate treatment for OS, a deeper understanding of its complex tumor microenvironment (TME) is required. In the present study, tissues were isolated from six patients with OS, and then subjected to single-cell RNA sequencing (scRNA-seq) using a 10× Genomics platform. Multiplex immunofluorescence staining was subsequently used to validate the subsets identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
149
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(161 citation statements)
references
References 111 publications
12
149
0
Order By: Relevance
“…By analyzing differentiation gene signatures in cell clones of chondroblastic osteosarcomas, these authors revealed that malignant chondroblastic osteosarcoma cells could be transdifferentiated into malignant osteoblastic cells. Liu and colleagues further demonstrated the presence of particular osteoblastic clones within bone tumors that are at the starting position of differentiation paths [ 117 ]. This was the first evidence in patients that osteosarcoma cell clones may not develop independently but are linked by hierarchical relationships and derive or “differentiate” from each other as shown in other types of tumors [ 118 , 119 ].…”
Section: Mechanisms Of Metastasis Formationmentioning
confidence: 99%
“…By analyzing differentiation gene signatures in cell clones of chondroblastic osteosarcomas, these authors revealed that malignant chondroblastic osteosarcoma cells could be transdifferentiated into malignant osteoblastic cells. Liu and colleagues further demonstrated the presence of particular osteoblastic clones within bone tumors that are at the starting position of differentiation paths [ 117 ]. This was the first evidence in patients that osteosarcoma cell clones may not develop independently but are linked by hierarchical relationships and derive or “differentiate” from each other as shown in other types of tumors [ 118 , 119 ].…”
Section: Mechanisms Of Metastasis Formationmentioning
confidence: 99%
“…scRNA sequencing data were obtained from GSE162454 ( ) from the Gene Expression Omnibus (GEO) database ( 9 ). GSE162454 data were collected from conventional osteosarcoma biopsy samples taken before chemotherapy, and OS1-6 cases were included in our study.…”
Section: Methodsmentioning
confidence: 99%
“…Made available with technological advances, single-cell RNA sequencing (scRNA-seq) can resolve gene expression at the individual cell level and enable us to better explore and identify chemoresistant cells. Liu Y’s and Zhou Y’s first applied scRNA-seq to reveal the landscapes of tumor environments in osteosarcoma ( 9 , 10 ). Comparing the two techniques, scRNA-seq has higher sensitivity but higher cost, whereas bulk RNA-seq has more samples and reliably reflects the characteristics among populations.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Liu et al. showed that single-cell transcriptomics elucidated the complexity of the tumor microenvironment of treatment-naive osteosarcoma ( 13 ). Zhou et al.…”
Section: Introductionmentioning
confidence: 99%